HOLLOW PARTIAL DENTURE ANTERIOR RAHANG ATAS POST HEMIMAXILLECTOMY - Debby Saputera; Sukaedi Sukaedi (FKG Unlam, 2016)
ABSTRACT Background : The hollow partial denture is a prosthesis commonly used as an effective means for rehabilitating post hemimaxillectomy patients. The size and location of the defect usually influences the extent of impairment and difficulty in prosthetic rehabilitation. Retention, stability and support are the three majors factors in the management of rehabilitation patients. Purpose : Provide information about the management of patients post hemimaxillectomy with hollow partial denture. Case : Male patient aged 40 years came to the clinic specialist Prosthodontics Faculty of Dentistry Airlangga University with complaints want to made a new maxillofacial prosthesis because the old prosthesis fracture and often loose when chewing food and to talk feel disturbed. Case Management : Print maxilla and mandible, then make bite record, teeth arrangement and do the scraping on the palate area and some area were taken for cover hollow, acrylic procesing, reduction in denture hollow and hollow cover, hollow cover attachment process with hollow denture followed by the installation of hollow maxillary denture. Conclusion : hollow partial denture can be used as a rehabilitation post hemimaxillectomy. ABSTRAKLatar belakang : Gigi tiruan sebagian hollow adalah protesa biasa digunakan sebagai cara yang efektif untuk merehabilitasi pasien post hemimaxillectomy. Ukuran dan lokasi yang cacat biasanya mempengaruhi tingkat gangguan dan kesulitan dalam rehabilitasi prostetik. Retensi, stabilitas dan dukungan adalah tiga faktor utama dalam pengelolaan pasien rehabilitasi. Tujuan : Memberikan informasi tentang pengelolaan pasien post hemimaxillectomy dengan gigi tiruan sebagian hollow. Kasus : Pasien laki-laki berusia 40 tahun seorang buruh datang ke klinik spesialis prostodonsia Fakultas Kedokteran Gigi Universitas Airlangga dengan keluhan ingin dibuatkan protesa maksilofasial yang baru karena protesa yang lama klamernya patah serta sering lepas saat mengunyah makanan dan untuk bicara merasa terganggu. Tata laksana kasus : Mencetak rahang atas dan rahang bawah, kemudian membuat galangan gigit, menyusun gigi dan melakukan pengerokan pada daerah palatum dan sebagian malam diambil buat penutup hollow, procesing akrilik, pengurangan pada gigi tiruan hollow dan penutup hollow, proses perlekatan penutup hollow dengan gigi tiruan hollow dilanjutkan dengan pemasangan gigi tiruan hollow rahang atas. Kesimpulan : gigi tiruan sebagian hollow dapat dipakai sebagai rehabilitasi post hemimaxillectomy.